Mathematical and experimental investigation of the ball type centrifugal clutch - Turkbay, Ismail (Gazi Univ, Fac Engineering Architecture, 2016)
In this study, the ball type centrifugal clutch was examined mathematically and experimentally. In the experiments, depending on the ball diameter variations; the transmitted torques were measured for various gap factor and spindle speed levels. The torque transmitted by the ball type centrifugal clutch is equal to the total of torques transmitted at the inner and two side surfaces. The smaller the ball diameter, the greater torque was transmitted. The ball type centrifugal clutch is used the areas where the running operation of the electric motor is required under the load. The clutch saves energy during the initial operation, and it behaves like a safety clutch at the over loading levels by sliding. The maximum transmittable torque can be adjusted by changing the mass of the ball in the housing.
Bilyali tip santrifüj kavramanin matematiksel ve deneysel incelenmesi
Keywords: Centrifugal clutch; ball type centrifugal clutch; porosity; torque